A liderança no contexto das redes organizacionais - Jair Nascimento Santos (2003)
This thesis was developed in the Work Relations and Management Technologies Department of the Federal University of Minas Gerais (Brazil), having as its basic assumption that there is a differentiated manifestation of leadership in the environment of organizationalnetworks, whatever their nature is, because of the social, structural and organizational settings that are elaborated to satisfy common objectives of network participants. Thus, our problem was the following: how the discourse, practices and development of leadership in the contextof the organizational networks are articulated, considering that the predominant rationality is still the instrumental one? Our objective was to carry out an analysis concerning the emergence of leadership in the context of organizational networks, incorporating multidisciplinary contributions of sociology, anthropology, psychology, symbolism andadministration, and establishing some organizational characteristics of leadership in the rearrangements and transformations. Our methodological approach searched a qualitative apparatus from data collected during interviews carried through with leaders in networksorganized by the following organizations: the Urban Cleaning Services of Belo Horizonte City Municipal Government, state of Minas Gerais; the Paper and Recyclable Materials Collectors Association; and the Committee of Industrial Development of Camaçari in the Petrochemical Polar region of Camaçari, State of Bahia. Our theoretical approach converged from the theory of organizations and structure, as a support to migrate, after that, to the contents on organizational networks. In the passage of contents from networks to leadership, we have approached subjects related to institutionalism and rizomas. The theoretical referenceon leadership went beyond the traditional texts on the subject and the critical analyses. The research results indicate the emergence of a leadership anchored in the reality of organizational, social, economic and political daily life, mainly for the understanding of the necessity of reduction of distance between the leader and the group. The study of leadership in the context of the organizational networks validates the perception that the contents of traditional literature on networks and leadership presents a gap in relation to the lived reality.